ANALISIS PENGEMBANGAN HUMAN CAPITAL, BUDAYA KERJA DAN KESESUAIAN PENEMPATAN PEGAWAI TERHADAP KINERJA PEGAWAI CABANG DINAS PENDIDIKAN WILAYAH PASURUAN - Arianto, Agus; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to identify and analyze the influence of human capital development, work culture, and employee placement suitability on employee performance at the Pasuruan Regional Education Office Branch. The research employs a quantitative approach using a census method, where the entire population of 52 employees was used as the research sample. Data analysis was conducted using multiple linear regression to examine both simultaneous and partial effects of the independent variables. The results indicate that, collectively, human capital development, work culture, and employee placement suitability have a significant effect on employee performance. Partially, each of these variables also has a positive influence on employee performance. Among the three, human capital development was found to have the most dominant influence on improving employee performance. These findings suggest that enhancing the quality of human resources through the development of employee competencies and potential is key to achieving better organizational performance.